PENGARUH MOTIF MENONTON PROGRAM BERITA “WARTA RIAU” TELEVISI REPUBLIK INDONESIA (TVRI) TERHADAP KEPUASAN INFORMASI MASYARAKAT DI KELURAHAN LABUHBARU TIMUR KECAMATAN PAYUNG SEKAKI PEKANBARU - Lasmawati "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Mass media especially television has choosen by audiences to get information. It is important role for television media to survive on their existence displayed programs which attract the audiences. The audiences needs of information media if fulfilled by impressions on mass media. According to uses and gratification theory explained about audiences rights to choose on which media that could fill their needs after consumed it. Television station in Indonesia using rating system as reference on making news program, nevertheless these rating system does not necessarily measure the satisfaction of audiences. To determine the audiences satisfaction with gratification sought and gratification obtained. The purpose of this research was to determine how much influence the motive watch news program “Warta Riau” Televisi Republik Indonesia (TVRI) for satisfaction of the information society in East Labuhbaru Subdisdrict Payung Sekaki District Kecamatan Pekanbaru.This research used quantitative methods with descriptive explanation. Researcher collected data using questionnaires. The study site is in East Labuhbaru Payung Sekaki Kecamatan District Pekanbaru. The sampling is done by using accidental sampling, with unknown population formulas and got 100 respondent. To figure out how big this two variable relate researcher using correlation analysis person product moment. Meanwhile for processing questionnaires data is done with statistic of service solution (SPSS) programs windows version 22.This study has shown that the effect watching motive of news program “Warta Riau” Televisi Republik Indonesia (TVRI) for satisfaction society of East Labuhbaru Payung Sekaki Subdistrict Pekanbaru. That the value R = 0,631 and the coefficient of determination (R2) = 0,398, which implies that the effect of independent variable (motive) on the dependent variable is 39,8 %, while the rest 60,2 % got influenced by other factors outside variable. This showing that level of significance is 0,001 smaller than α = 0,05 it means the effect to satisfaction based on motive variable is 39,8 % which categorized low influence.Keyword : influence, motive, program, satisfaction of the information